Process of Physical Activity Associated with Health Care Behaviors of Thai Elderly Systematic Revie - เรืองสิทธิ์ วัชราภรณ์; วงษ์ประเสริฐ จำลอง; กุลประฑีปัญญา กุลธิดา (Nursing Journal of The Ministry of Public Health, 2018)
The purposes of this systematic review were to review the literature, synthesisand summarizing to the knowledgeabout process of physical activities associated with health care behaviors of Thai elderly. A systematic review of the literature was selected from existing evidence electronic databases. The samples of research were 98 research studies, published during 2007-2016. Results of this studied were found process of physical activities associated with health care behaviors of Thai elderly including 1) education program such as health promotion program, empowerment program, counseling program, self-efficacy program, self-management promotion program 2)exercise activities 3) group process 4) meditation practice and 5) art and music activities . Finding of systematic review indicate that the conclusion can explainprocess of physical activities associated with health care behaviors of Thai elderly. This is benefit for guideline practice in order to promote the elderly to practice health care behaviors sustainably.